Isolated Distal Pancreatic Transection Secondary to an Abdominal Blunt Trauma - A Case Report - AA Medina Velasco; JM Ramia; V Arteaga Peralta; J Valenzuela; AJ Lopez Marcano (Archives of Clinical Gastroenterology - Peertechz Publications, 2016)
Isolated pancreatic trauma (IPT) secondary to an abdominal blunt trauma, is an uncommon condition- IPT diagnosis usually is insidious, requiring the integration of multiple parameters, regarding anamnesis, physical examination, blood analysis and radiologic tests. Nowadays, exists controversy in the literature about management of the IPT. We report a case of a young male with a body-tail pancreatic transection, secondary to an abdominal blunt trauma. Distal pancreatectomy with spleen preservation was performed with successful postoperative course. We discuss diagnostic and therapeutical options in IPT.